PENGARUH RELAKSASI PROGRESIF TERHADAP KECEMASAN PADA PASIEN PRE OPERASI DI RUMAH SAKIT BHAYANGKARA MAKASSAR - Rusli Taher (Stikes Graha Edukasi Makassar, 2019)
Objective: to study the interaction of progressive relaxation on the level of openness in preoperative patients at the Bhayangkara Hospital in Makassar. Method: This study used a pre-experimental design using a purposive sampling technique with a sample of 16 respondents who would carry out operations at the Bhayangkara Hospital Makassar. Data collection using questionnaire sheets. Results: The results of the study showed that from 16 respondents, there were significant differences. From the results of the Wilcoxon test with a p value = 0,000 smaller than alpha = 0.05 (p value = ?). Refusing H0 is rejected and accepted, so it can be canceled, of course there is progressive relaxation towards the level of consideration in patients before surgery. Discussion: Preoperative nursing is the initial stage of perioperative nursing. The preoperative phase begins with compilation taken for surgical intervention. Anxiety is a normal adaptive response to stress due to surgery. Anxiety usually arises in preoperative patients compiling surgical patients, changes in body image and bodily functions. Conclusion: There was a relaxation of progressive relaxation before and after relaxation techniques were performed against the decrease in anxiety in Bhayangkara Hospital, Makassar. Suggestion: It is expected that nurses can carry out progressive relaxation techniques in preoperative patients who increase the comfort of health services to the level of patient progress.